THE ROLE OF THE POLICE IN DEALING WITH THE CRIME OF THEFT WITH VIOLENCE THAT OCCURS IN THE JURISDICTION DELI SERDANG POLICE STATION - Reza Anwar; Danial Syah; Cut Nurita (Jurnal Ilmiah METADATA, 2026)
Theft with violence from a legal perspective is one of the criminal acts that is troubling and detrimental to the community. The role of the police in dealing with the crime of theft with violence (curas) is very important, including preventive and repressive measures. Preventively, the police conduct patrols, provide counseling to the community, and increase cooperation with the community. Repressively, the police investigate, arrest the perpetrators, and bring the case to court. The efforts of the law enforcement officers of the Deli Serdang City Resort Police in tackling theft with violence are preventive efforts. Repressive efforts (enforcement) are analyzing recidivist data, forming a special team to uncover, analyze and evaluate each incident that occurs.